2014
DOI: 10.1038/srep07352
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Layered MoS2 Biosensors Enable Highly Sensitive Detection of Biomolecules

Abstract: We present a MoS2 biosensor to electrically detect prostate specific antigen (PSA) in a highly sensitive and label-free manner. Unlike previous MoS2-FET-based biosensors, the device configuration of our biosensors does not require a dielectric layer such as HfO2 due to the hydrophobicity of MoS2. Such an oxide-free operation improves sensitivity and simplifies sensor design. For a quantitative and selective detection of PSA antigen, anti-PSA antibody was immobilized on the sensor surface. Then, introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
232
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(241 citation statements)
references
References 30 publications
6
232
1
2
Order By: Relevance
“…The detection of the same cancer biomarker was also reported by Lee et al [50]. The team presented a MoS 2 -FET biosensor that does not require a dielectric layer due to the hydrophobicity nature of MoS 2 , which allows the direct adsorption of antibodies and an improved sensitivity of the device.…”
Section: Molybdenum Disulfidementioning
confidence: 76%
See 1 more Smart Citation
“…The detection of the same cancer biomarker was also reported by Lee et al [50]. The team presented a MoS 2 -FET biosensor that does not require a dielectric layer due to the hydrophobicity nature of MoS 2 , which allows the direct adsorption of antibodies and an improved sensitivity of the device.…”
Section: Molybdenum Disulfidementioning
confidence: 76%
“…It is evident that a great diversity of disease biomarkers can be detected through immunoFET devices, opening new paths for early-stage diagnosis of serious diseases such as cancer. For instance, prostate specific antigen (PSA), a prostate cancer biomarker, was ultrasensitively detected by using immunoFET devices based on different nanomaterials such as silicon nanowires (SiNW) [47,48], graphene [49], molybdenum disulfide (MoS 2 ) [50,51], etc. The lowest detection limit of PSA was achieved by a FET device based on SiNW (1 fg·mL −1 ) [47].…”
Section: Trends In Fet-based Immunosensors Using Nanomaterials As Senmentioning
confidence: 99%
“…[161][162][163][164] Using rst-principles calculations, Yue et al found that small gas molecules can be physically absorbed on monolayer MoS 2 , and determined the most stable adsorption conguration and adsorption energy. 165 The band structure of monolayer MoS 2 will not signicantly be altered though small gas molecules are absorbed.…”
Section: Sensor and Detectormentioning
confidence: 99%
“…[13][14][15][16] However, 1D semiconductor biosensors still have limitations such as device-to-device performance variation, non-uniformity, and a small integration area. 17,18 2D layered semiconductor-based sensors with a high surface-to-volume ratio have fewer limitations than 1D semiconductor biosensors. 2D devices offer highly sensitive detection for biomolecules and ions and serve as the basis for conventional planar devices in large-area integration.…”
mentioning
confidence: 99%
“…17 PSA antibodies adsorbed on the MoS 2 surface yield SP variations on the FET surface, resulting in varying I-V characteristics. However, the correlation between the amount of adsorbed PSA antibody and electrical performance remains unclear.…”
mentioning
confidence: 99%